Smart Building Design : Conception, Planning, Realization, and Operation - Bali, Maad; Half, Dietmar A.; Polle, Dieter (Birkhäuser, 2019)
How can smart technology open up new design opportunities - for the design, the execution, and the operation of buildings and for the digitalization of construction? A hitherto unusual conception of the building as a cybernetic architectural system forms the basis of this integrated design approach. The authors - architects and engineers with extensive design experience - contribute an overview of current technical components of automation and communication systems, as well as a summary of relevant laws, standards, and guidelines. Six example projects demonstrate completed applications at different scales, from a single-family residence to office buildings, and through to the Elbphilharmonie concert hall - amply illustrated in text, drawings, and photos.